PENDEKATAN KOMUNIKASI KEPEMIMPINAN LEMBAGA DAKWAH: GAYA MANAJEMEN KONFLIK (INTEGRATING, OBLIGING, DOMINATING, AVOIDING, COMPROMISING) - Fadilah, Nurul; Castrawijaya, Cecep (Jurnal Al-Hikmah: Jurnal Dakwah, 2024)
The purpose of this study is to contribute ideas and introduce a communication approach to the leadership of da'wah institutions. This study departs from the root of the problem or individual conflicts that often occur in a group, especially groups of da'wah institutions, and basically every group needs a figure who can lead massively so that cooperation between groups can run according to goals. Through the identification of phenomena and literature studies that might be considered as a way to solve or manage conflicts in organizational groups using the concept of conflict management styles according to Rahim (2001) integrating, obliging, dominating, avoiding, and compromising. The results of his research show that conflict management in the leadership of da'wah institutions involves choosing the right style, such as collaborative, yielding, dominating, avoiding, and compromising, according to the situation at hand. An effective leader must be able to choose the appropriate style to maintain harmony and achieve organizational goals, taking into account the advantages and disadvantages of each style. Wise selection of styles will help resolve conflicts efficiently and ensure smooth communication within the da'wah institution.[Tujuan dari penelitian ini untuk memberikan sumbangsih ide dan memperkenalkannya sebuah pendekatan komunikasi kepemimpinan lembaga dakwah. Kajian ini berangkat dari akar problem atau konflik individu yang sering terjadi dalam suatu kelompok, khususnya kelompok lembaga dakwah, dan pada dasarnya setiap kelompok membutuhkan sosok yang dapat memimpin secara massive agar kerjasama antar kelompoknya dapat berjalan sesusai dengan tujuan. Melalui identifikasi fenomena dan studi literatur yang mungkin dapat dipertimbangkan sebagai suatu cara untuk memecahkan atau memanajemen konflik di dalam kelompok organisasi dengan menggunakan konsep gaya manajemen konflik menurut Rahim (2001) integrating, obliging, dominating, avoiding, and compromising. Hasil penelitiannya menunjukkan manajemen konflik dalam kepemimpinan lembaga dakwah melibatkan pemilihan gaya yang tepat, seperti kolaboratif, mengalah, mendominasi, menghindar, dan kompromi, sesuai dengan situasi yang dihadapi. Pemimpin yang efektif harus mampu memilih gaya yang sesuai untuk menjaga keharmonisan dan mencapai tujuan organisasi, dengan mempertimbangkan kelebihan dan kelemahan setiap gaya. Pemilihan gaya yang bijaksana akan membantu menyelesaikan konflik secara efisien dan memastikan kelancaran komunikasi dalam lembaga dakwah.]